Valores do dinheiro: uma análise da influência da percepção do dinheiro na escolha da profissão - Oliveira, Júlio César de Vargas (2010)
The present study sought to determine the influence of perceptions of money in the choice of profession by undergraduate students. To do this, the questionnaires were applied with both respondents 1,139 educational institutions from public and private. The data were analyzed by factor analysis, statistical tests (ANOVA, t Test and correlation) and regression analysis. In factor analysis, were validated 14 factors (Conflict, Happiness, Power, Concern, Sociocultural, Detachment, Complexity, Evolution, Social Status, Social Inequality, Stability, Pleasure, Technological Development and Social Equity). Among the determining factors in the choice of profession, high remuneration has occupied the third place on the scale of importance, second only to personal fulfillment and the labour market. In the first model of regression analysis, was found a positive relationship of Happiness factor associated with the money and a negative relationship to the Socio-cultural Development factor linked to money. In the second model of regression analysis, whose idea that professions who earn more money are the most valued, the positive influence of factors Happiness, Social Status, Technological Development, Social Inequality and Conflict, and a negative influence of factors Stability and Concern. Students interviewed had higher average for the factor linked to money Evolution, indicating the idea of claim with respect to investment that are performing in education. The ANOVA test found no significant difference in the variables marital status, religion, religious principles, area of expertise of the degree course, race, ancestry and family group's income. In regression analysis was found a positive relationship of Happiness factor associated with the money and a negative relationship to the Socio-cultural Development factor linked to money.